2019
DOI: 10.1371/journal.pone.0220904
|View full text |Cite
|
Sign up to set email alerts
|

Absolute expressions of hypoxia-inducible factor-1 alpha (HIF1A) transcript and the associated genes in chicken skeletal muscle with white striping and wooden breast myopathies

Abstract: Development of white striping (WS) and wooden breast (WB) in broiler breast meat have been linked to hypoxia, but their etiologies are not fully understood. This study aimed at investigating absolute expression of hypoxia-inducible factor-1 alpha subunit ( HIF1A ) and genes involved in stress responses and muscle repair using a droplet digital polymerase chain reaction. Total RNA was isolated from pectoralis major collected from male 6-week-old medium (carcass weight ≤ 2.5 kg) and heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
52
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 104 publications
(151 reference statements)
10
52
2
Order By: Relevance
“…A recent study performed in broiler where they studied time series differential expression of genes in WB affected P. major using RNAseq showed molecular perturbations involving vasculature in early pathogenesis (32). Similarly, another study found the genes related to hypoxia were upregulated in WB affected muscle fibers (33), and microscopical morphometry of vessel density in muscle showed the compromised blood supply in affected tissue (34). Additionally, P. major histological or compositional analysis have exhibited increased lipid content in tissue as an important attribute of muscle myopathy (6,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…A recent study performed in broiler where they studied time series differential expression of genes in WB affected P. major using RNAseq showed molecular perturbations involving vasculature in early pathogenesis (32). Similarly, another study found the genes related to hypoxia were upregulated in WB affected muscle fibers (33), and microscopical morphometry of vessel density in muscle showed the compromised blood supply in affected tissue (34). Additionally, P. major histological or compositional analysis have exhibited increased lipid content in tissue as an important attribute of muscle myopathy (6,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 96%
“…Prior systematic studies of the abnormal muscle phenotype referred to as wooden breast using gene expression measurements has identified multiple processes that may contribute to the development of the myopathy. Processes including muscle fiber regeneration, inflammatory response, myodegeneration, hypoxia, fibrosis, lipidosis, and altered energy metabolism are likely involved in the manifestation of wooden breast (Mutryn et al, 2015;Zambonelli et al, 2016;Papah et al, 2018;Malila et al, 2019;Petracci et al, 2019). This study attempts to connect organismal level physiology and metabolism with the activity in the breast muscle by including the evaluation of liver gene expression by a novel analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of WB is currently unknown, but it is more prevalent in older, heavier male broilers than young birds (Kuttappan et al, 2017;Brothers et al, 2019). Larger breast muscle has been associated with hypertrophied muscle fibers which is thought to impact blood supply and number of satellite cells that are needed in muscle regeneration (Daughtry et al, 2017;Malila et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The specific origin of these myopathies has not been well elucidated. Recent findings have linked their onset with hypoxia (Malila et al, 2019) due to reduced vascularization (Sihvo et al, 2018), phlebitis (Papah et al, 2017;Chen et al, 2019), and glucolipotoxicity (Mutryn et al, 2015;Abasht et al, 2016;Lake and Abasht, 2020). The final result is a muscle with defective energy-generating pathways combined with a deficiency and/or dysfunction of tissue ATPases, having consequences in myodegeneration and on muscle fiber contraction degree (Baldi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%